Iterative Methods for Solving Nonlinear Equations with Fourth-Order Convergence - Jnawali, Jivandhar; Bhatta, Chet Raj (Tribhuvan University Journal, 2016)
In this paper, we obtain fourth order iterative method for solving nonlinear equations by combining arithmetic mean Newton method, harmonic mean Newton method and midpoint Newton method uniquely. Also, some variant of Newton type methods based on inverse function have been developed. These methods are free from second order derivatives.